Study of the Structure of Borromean Nucleus 17^Ne - 王恩宏 华辉 卢飞 叶沿林 李智焕 江栋兴 李湘庆 葛愉成 郑涛 宋玉收 (Plasma science & technology, 2012)
In the present research, we used the 17^Ne beam at 30.8 MeV/u to bombard the 43 mg/cm^2 12^C target and measured the angular correlations between the fragments and emitted proton. In the break-up reaction of 17^Ne, one-proton knockout would result in an unstable nu- cleus 16^F, which would further decay by the proton emission. The measured angular correlation between the 16^F momentum and the relative momentum of its decay products was compared with theoretical calculations and indicated that the valence proton in 17^Ne has the most probability to be situated in the s1/2 orbital with a small admixture of the d5/2 orbital. The present results suggest that 17^Ne has a halo structure.